Cell- and Lamina-Specific Expression and Activity-Dependent Regulation of Type II Calcium/Calmodulin-Dependent Protein Kinase Isoforms in Monkey Visual Cortex - Tighilet, Brahim; Hashikawa, Tsutomu; Jones, Edward G (The Journal of neuroscience, 1998)
In situ hybridization histochemistry and immunocytochemistry were used to study localization and activity-dependent regulation of α, β, γ, and δ isoforms of type II calcium/calmodulin-dependent protein kinase (CaMKII) and their mRNAs in areas 17 and 18 of normal and monocularly deprived adult macaques. CaMKII-α is expressed overall at levels three to four times higher than that of CaMKII-β and at least 15 times higher than that of CaMKII-γ and -δ. All isoforms are expressed primarily in pyramidal cells of both areas, especially those of layers II–III, IVA (in area 17), and VI, but are also expressed in nonpyramidal, non-GABAergic cells of layer IV of both areas and in interstitial neurons of the white matter. CaMKII-α and -β are colocalized, suggesting the formation of heteromers. There was no evidence of expression in neuroglial cells. Each isoform has a unique pattern of laminar and sublaminar distribution, but cortical layers or sublayers enriched for one isoform do not correlate with layers receiving inputs only from isoform-specific layers of the lateral geniculate nucleus. CaMKII-α and -β mRNA and protein levels in layer IVC of area 17 are subject to activity-dependent regulation, with brief periods of monocular deprivation caused by intraocular injections of tetrodotoxin leading to a 30% increase in CaMKII-α mRNA and a comparable decrease in CaMKII-β mRNA in deprived ocular dominance columns, especially of layer IVCβ. Expression in other layers and expression of CaMKII-γ and δ were unaffected. Changes occurring in layer IVC may influence the formation of heteromers and protect supragranular layers from CaMKII-dependent plasticity in the adult.